2013
DOI: 10.7314/apjcp.2013.14.11.6687
|View full text |Cite
|
Sign up to set email alerts
|

Survival Analysis and Prognostic Factors for Neuroendocrine Tumors in Turkey

Abstract: 1-90 months). The three-year overall survival rate was 71%: 100% in stage I, 88% in stage II, 80% in stage III, and 40% in stage IV. The three-year survival rate was 78% in tumors localized in the gastroenteropancreatic region, and 54% in tumors localized in other organs. In the univariate analysis, gender, age, performance status of the patients, grade, localization, surgical treatment, and neutrophil/ lymphocyte ratio (≤5 versus >5) affected the prognosis of the patients. Conclusions: Most of the tumors were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
(33 reference statements)
2
22
1
Order By: Relevance
“…The primary origin of the tumor was unknown in 32 patients. Our results are in accordance with a similar conducted research in Turkey in which gastrointestinal and lung have been reported as major sites of neuroendocrine tumors (Yocel, et al 2013). In a study by Sorbye and colleagues the primary tumor site was pancreas and colon in 64 patients (Sorbye et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…The primary origin of the tumor was unknown in 32 patients. Our results are in accordance with a similar conducted research in Turkey in which gastrointestinal and lung have been reported as major sites of neuroendocrine tumors (Yocel, et al 2013). In a study by Sorbye and colleagues the primary tumor site was pancreas and colon in 64 patients (Sorbye et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with other studies, our study demonstrates improved survival rates with curative surgery (23)(24)(25). A multidisiplinary approach, including surgery, somatostatin analogues, chemotherapy, targeted therapy, and peptide receptor radionuclide therapy (PRRT), should be considered, and treatment should be individualized for patients with NETs.…”
Section: öZaslan Et Al Prognostic Factors Of Neuroendocrine Tumorssupporting
confidence: 65%
“…Pulmonary NET could be clinically, radiologically, and pathologically classified into four subtypes: TC, AC, LCNEC and SCLC (Haghighi et al, 2012;Liu et al, 2013;Yucel et al, 2013;Zahir et al, 2013;Zeng et al, 2013). They represent a specific group of tumors with heterogeneous histological patterns and clinical behaviors.…”
Section: Discussionmentioning
confidence: 99%